Canada : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2019)
This Financial System Stability Assessment paper discusses that Canada has enjoyed favorable macroeconomic outcomes over the past decades, and its vibrant financial system continues to grow robustly. However, macrofinancial vulnerabilities-notably, elevated household debt and housing market imbalances-remain substantial, posing financial stability concerns. Various parts of the financial system are directly exposed to the housing market and/or linked through housing finance. The financial system would be able to manage severe macrofinancial shocks. Major deposit-taking institutions would remain resilient, but mortgage insurers would need additional capital in a severe adverse scenario. Housing finance is broadly resilient, notwithstanding some weaknesses in the small non-prime mortgage lending segment. Although banks' overall capital buffers are adequate, additional required capital for mortgage exposures, along with measures to increase risk-based differentiation in mortgage pricing, would be desirable. This would help ensure adequate through-the cycle buffers, improve mortgage risk-pricing, and limit procyclical effects induced by housing market corrections.